Two-terminal fault detection and location for hybrid transmission circuit - Muhd Hafizi Idris; Mohd Rafi Adzman; Hazlie Mokhlis; Mohammad Faridun Naim Tajuddin; Haziah Hamid; Melaty Amirruddin (Institute of Advanced Engineering and Science, 2021)
This paper presents the algorithms developed to detect and locate the faults ata hybrid circuit. First, the fault detection algorithm was developed using the comparison of total positive-sequence fault current between pre-fault and fault times to detect the occurrence of a fault. Then, the voltage check method was used to decide whether the fault occurred at overhead line (OHL) or cable section. Finally, the fault location algorithm using the impedance-based method and negative-sequence measurements from both terminals of the circuit were used to estimate the fault point from local terminal. From the tests of various fault conditions including different fault types, fault resistance and fault locations, the proposed method successfully detected all fault cases at around 1 cycle from fault initiation and with correct faulted section identification. Besides that, the fault location algorithm also has very accurate results of fault estimation with average error less than 1 km and 1%.